2008
DOI: 10.7150/ijms.5.263
|View full text |Cite
|
Sign up to set email alerts
|

Eph Receptors and Ephrin Signaling Pathways: A Role in Bone Homeostasis

Abstract: The maintenance of bone homeostasis is tightly controlled, and largely dependent upon cellular communication between osteoclasts and osteoblasts, and the coupling of bone resorption to bone formation. This tight coupling is essential for the correct function and maintenance of the skeletal system, repairing microscopic skeletal damage and replacing aged bone. A range of pathologic diseases, including osteoporosis and cancer-induced bone disease, disrupt this coupling and cause subsequent alterations in bone ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 87 publications
(88 reference statements)
1
112
0
2
Order By: Relevance
“…As expected, EphB4-Fc blocked OB differentiation ( Figure 3C) and suppressed OCL differentiation by inhibiting the c-Fos/NFATc1 cascade (Figure 3, D-F), as reported in other models (16). Interestingly, EphB4-Fc treatment also decreased IL-6 and IGF1 expression in these cocultures.…”
Section: and Il6supporting
confidence: 63%
See 2 more Smart Citations
“…As expected, EphB4-Fc blocked OB differentiation ( Figure 3C) and suppressed OCL differentiation by inhibiting the c-Fos/NFATc1 cascade (Figure 3, D-F), as reported in other models (16). Interestingly, EphB4-Fc treatment also decreased IL-6 and IGF1 expression in these cocultures.…”
Section: and Il6supporting
confidence: 63%
“…We found that IL-6 (10 ng/ml) also increased ephrinB2 expression on OCLs derived from CD11b + cells from WT mice ( Figure 4D) as well as EphB4 expression in WT OBs ( Figure 4F). Interestingly, IL-6 only induced ephrinB2 expression in MVNP-transduced human OCLs (Figure 4E), suggesting that another factor induced by MVNP cooperates with IL-6 to increase ephrinB2 expression in receptors promote skeletal development (16). Zhao and coworkers showed that bidirectional ephrinB2/EphB4 signaling regulates bone remodeling (15), that OCLs express the NFATc1 target gene ephrinB2 and OBs express its receptor EphB4, and that transgenic mice with increased EphB4 signaling in OBs had enhanced bone mass (15).…”
Section: Il-6 Increases Ephrinb2 and Ephb4 Expression Onmentioning
confidence: 97%
See 1 more Smart Citation
“…blast lineage cells) and the bone-resorbing osteoclasts, a process namely bone remodeling. The balance between the two activities is under the spatio-temporal control of several signaling pathways (1)(2)(3)(4)(5). Any interrupttion of the balance between osteoblasts and osteoclasts can compromise bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-surface molecules, such as receptors and their associated ligands, play a role in the maintenance of bone homeostasis (Edwards and Mundy, 2008). EphrinB2 and EphB4 mediate osteoclast-osteoblast interactions by simultaneous signal transduction in both cells.…”
Section: Introductionmentioning
confidence: 99%